A FEW CONSIDERATIONS ON DRAMA TRANSLATION - Tatu Oana (My University, 2011)
The translation of literary texts is, as a rule, a difficult task, and it basically requires talent, patience, linguistic and extra-linguistic knowledge. Furthermore, drama translation compounds the issue and claims, besides all the above mentioned qualities, the translator’s awareness of the dual nature that drama displays: a text written for an audience and performed on stage, or a text written for readers and laid down on page. This dual nature will necessarily be rendered in translation.
Keywords: drama; translation; performance; book form